A study to assess predictive value of yolk sac diameter by transvaginal sonography with the pregnancy outcome - Sheik, Saniya; B., Anjana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Ultrasonography is one of the most important and useful diagnostic tools in the field of modern medicine. Being non-invasive, safe and without hazards of radiation, it has gained wide acceptability, as an integral part of basic investigative procedures. A yolk sac can be detected easily by transvaginal sonography when the mean gestational sac diameter is 5 to 6 mm. Generally, the yolk sac should be observed when a gestational sac measures greater than 8. The yolk sac is situated between the amnion and the chorion. Methods: The present Prospective study was conducted in the department of obstetrics and gynecology, K. L. E. S. Dr. Prabhakar Kore charitable Hospital and Medical Research Centre, Belagavi during the period of January 2015 to February 2016. Records of pregnant women registering between 6 to 10-week 6 days’ period of gestation in OPD at KLES Dr. Prabhakar Kore Charitable Hospital and Medical Research Centre, Belagavi and who were fulfilling eligible selection criteria were studied prospectively. Results: A total of 254 study participants were included in the study and analysed. In this study, 49 cases were from age group of 20 years or less than 20 years i.e. around 19.29% of total study population. Majority of the cases were with normal yolk sac diameter (YSD) i.e. around 201 cases which accounts for 79.13% of total study population and total number of cases with abnormal yolk sac diameter (YSD) were 53 which accounts for 20.87% of total study population. Conclusions: Measurement of the secondary yolk sac diameter between 6th to 10th weeks 6 days of gestation can be used as a valuable tool in predicting outcome of the pregnancy.